Baseline Studies of Terrestrial Outdoor Gamma Dose Rates of Ten Selected Markets in Port Harcourt Metropolis - C. P. Ononugbo; S. Oduware (Archives of Current Research International, 2017)
In-situ measurement of background ionizing radiation of 10 markets in Port Harcourt metropolis of Rivers State, Nigeria was done using radiation meters and global positioning system. Two portable handheld nuclear radiation monitors (radalert100 and digilert200) to measure exposure dose rate at the various points and a GPS (Germin GPS map 76S for exact positions. The average exposure rates ranged from 0.011 mRh-1 (Mile 1 market) to 0.017 mRh-1 (Rukpokwu international market). The exposure dose rate measured at Rumuodomaya slaughter market (H). Rumuokoro market and Rukpokwu international market (J) were higher than the permissible value of 0.013 mRh-1. The absorbed dose rate of all the ten markets exceeded the world average value of 84.0 nGyh-1 while the annual effective dose calculated for all the markets were lower than the permissible value. The cancer risk parameter estimated (excess lifetime cancer risk) of all the markets exceeded the permissible value of 0.29 × 10-3. The result of this work gives the baseline radiation status of those markets sampled.